Lacunae rostralis: A new structure on the rostrum of sailfish Istiophorus platypterus. Issue 5 (9th March 2022) - Häge, Jan; Hansen, Matthew J.; Pacher, Korbinian; Dhellemmes, Félicie; Domenici, Paolo; Steffensen, John F.; Breuker, Michael; Krause, Stefan; Hildebrandt, Thomas B.; Fritsch, Guido; Bach, Pascal; Sabarros, Philippe S.; et al.
Abstract: Recent comparative studies of billfishes (Istiophoridae and Xiphiidae) have provided evidence of differences in the form and function of the rostra (bill) among species. Here, we report the discovery of a new structure, lacuna rostralis, on the rostra of sailfish Istiophorus platypterus, which is absent on the rostra of swordfish Xiphias gladius, striped marlin Kajikia audax and blue marlin Makaira nigricans . The lacunae rostralis are small cavities that contain teeth. They were found on the ventral rostrum surface of all I. platypterus specimens examined and dorsally in half of them. Ventrally, the lacunae rostralis were most prominent in the mid‐section of the rostrum. Dorsally, they occurred closer to the tip. The density of lacunae rostralis increased towards the rostrum tip but, because they are smaller in size, the percentage of rostrum coverage decreased. The teeth located within the lacunae rostralis were found to be different in size, location and orientation from the previously identified micro‐teeth of billfish. We propose two potential functions of the lacunae rostralis that both relate to the use of the bill in feeding: mechanoreception of prey before tapping it with the bill and more efficient prey handling via the creation of suction, or physical grip.